Population studies of the fragile X: a molecular approach. - Jacobs, P A (1993)
The fragile X mutation can now be recognised by a variety of molecular techniques. We report a pilot screening survey of a population of children with mental impairment in which we used Southern blotting methods to detect the fragile X mutation, augmented by cytogenetic studies on children whose phenotype suggested a possible chromosome abnormality. There were 873 children with special educational needs in our survey and 310 fulfilled our criteria for testing. A sample was obtained from 254, of whom four were found to have a full fra(X) mutation (delta L) and none to have a premutation. The number of CGG repeats in our population of X chromosomes was measured by PCR analysis and the genotype at the closely linked polymorphic locus FRAXAC1 established. The distribution of CGG repeat numbers was very similar to that of the control population reported by Fu et al and the distribution of FRAXAC1 alleles almost identical to that of the control population reported by Richards et al. Among the non-fragile X chromosomes, we found a very significant correlation between the size of the CGG repeat and the FRAXAC1 genotype. There was a dearth of A and D genotypes in subjects with a small number of CGG repeats and an excess of the A genotype in those with a large number of CGG repeats. These observations are considered in the light of the reported disequilibrium between the A (and possibly also the D) genotype and the fra(X) mutation.